Reactualization of Sundanese Local Hero Figure’s Values to Foster Student Character in History Education - Yulia Sofiani; Miftahul Habib Fachrurozi; Laely Armiyati (Paramita: Historical Studies Journal, 2025)
Abstract: This research aims to analyze the character values of Regent RAA Kusumadiningrat as one of the Sundanese local heroes and their relevance in the context of history education in the Kurikulum Merdeka. This study is qualitative research that adopts a multi-method research (MMR) strategy with a narrative approach and policy research approach. Data collection is conducted through documentation from primary and secondary sources related to Kusumadiningrat and Kurikulum Merdeka, interviews, and observations conducted at historical sites. Data analysis uses an interactive model owned by Miles and Huberman, which is carried out in an interactive form with the data collection process as part of the analysis cycle process, along with data condensation, display, and conclusion drawing/verification. The research results show that Kusumadiningrat, as a Sundanese traditional leader, has several character traits that are relevant to the Pancasila Student Profiles in the Kurikulum Merdeka, such as faith in God Almighty, critical thinking, global diversity, creative thinking, cooperation, and independence. Reactualization of Kusumadiningrat's character values can be carried out in the F-phase of the Kurikulum Merdeka, especially in the elements of understanding and skills of historical processes, which can be implemented through research project-based learning on this character. This study confirms the importance of promoting local hero values in history education and suggests a new perspective on local heroes that do not necessarily need to be defined by confrontation. Incorporating local heroes into the history education curriculum can serve as sources of inspiration for students, fostering their character development. Abstrak: Penelitian ini bertujuan menganalisis nilai-nilai karakter Bupati RAA Kusumadiningrat sebagai salah satu pahlawan lokal Sunda dan relevansinya dalam konteks pendidikan sejarah pada Kurikulum Merdeka. Studi ini merupakan penelitian kualitatif dengan strategi multi-method research (MMR) yang mengadopsi pendekatan naratif dan penelitian kebijakan. Pengumpulan data dilakukan melalui dokumentasi sumber primer dan sekunder terkait Kusumadiningrat dan Kurikulum Merdeka, wawancara, serta observasi di situs-situs sejarah. Analisis data menggunakan model interaktif Miles dan Huberman yang dilaksanakan secara interaktif bersamaan dengan proses pengumpulan data sebagai bagian dari siklus analisis, meliputi kondensasi data, penyajian data, dan penarikan/verifikasi kesimpulan. Hasil penelitian menunjukkan bahwa Kusumadiningrat sebagai pemimpin tradisional Sunda memiliki beberapa nilai karakter yang relevan dengan Profil Pelajar Pancasila dalam Kurikulum Merdeka, antara lain beriman kepada Tuhan Yang Maha Esa, berpikir kritis, berkebinekaan global, berpikir kreatif, bergotong royong, dan mandiri. Reaktualisasi nilai-nilai karakter Kusumadiningrat dapat dilaksanakan pada fase F Kurikulum Merdeka, khususnya pada elemen pemahaman dan keterampilan proses sejarah yang dapat diimplementasikan melalui pembelajaran berbasis proyek penelitian tentang tokoh ini. Studi ini menegaskan pentingnya mengangkat nilai-nilai pahlawan lokal dalam pendidikan sejarah serta menawarkan perspektif baru bahwa pahlawan lokal tidak harus selalu didefinisikan melalui konfrontasi. Integrasi pahlawan lokal dalam kurikulum pendidikan sejarah dapat menjadi sumber inspirasi bagi siswa dalam menumbuhkan perkembangan karakter.